A Benchmark for Multidimensional Statistical Data - Baumgärtel, Philipp; Endler, Gregor; Lenz, Richard (Advances in Databases and Information Systems, 2013)
ProHTA (Prospective Health Technology Assessment) is a simulation project that aims at estimating the outcome of new medical innovations at an early stage. To this end, hybrid and modular simulations are employed. For this large scale simulation project, efficient management of multidimensional statistical data is important. Therefore, we propose a benchmark to evaluate query processing of this kind of data in relational and non-relational databases. We compare our benchmark with existing approaches and point out differences. This paper presents a mapping to a flexible relational model, JSON documents and RDF. The queries defined for our benchmark are mapped to SQL, SPARQL, the MongoDB query language and MapReduce. Using our benchmark, we evaluate these different systems and discuss differences between them. © 2013 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD6.abench

A Query Language for Workflow Instance Data - Baumgärtel, Philipp; Lenz, Richard; Tenschert, Johannes (New Trends in Databases and Information Systems, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD6.aquery

Black-box Determination of Cost Models' Parameters for Federated Stream-Processing Systems - Daum, Michael; Lauterwald, Frank; Baumgärtel, Philipp; Pollner, Thomas Niko; Meyer-Wegener, Klaus (Proceedings of the 15th Symposium on International Database Engineering & Applications, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD6.blackb
Keywords: optimization techniques; heterogeneous event-based systems; data stream systems; performance modeling; cost models; calibration; black-box parameter Determination; DSAM

Data quality for managers of medical supply centers - Endler, Gregor; Baumgärtel, Philipp; Held, Johannes; Lenz, Richard (GMDS 2012, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD6.dataqu_2
Keywords: data quality; population completeness

Efficient and Cost-aware Operator Placement in Heterogeneous Stream-Processing Environments - Daum, Michael; Lauterwald, Frank; Baumgärtel, Philipp; Pollner, Thomas Niko; Meyer-Wegener, Klaus (Proceedings of the 5th ACM International Conference on Distributed Event-Based Systems, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD6.effici
Keywords: DSAM; Data Stream Application Manager; linear programming relaxation; iterative deterministic rounding; task assignment problem; operator placement; distributed data stream processing

ForCE: Is Estimation of Data Completeness Through Time Series Forecasts Feasible? - Endler, Gregor; Baumgärtel, Philipp; Wahl, Andreas Maximilian; Lenz, Richard (Advances in Databases and Information Systems, 2015)
Measuring the completeness of a data population often requires either expert knowledge or the presence of reference data. If neither is available, measuring population completeness becomes nontrivial. We present the ForCE approach (Forecasting for Completeness Estimation), a method to estimate the completeness of timestamped data using time series forecasting. We evaluate the method’s feasibility using a medical domain real-world dataset, which we provide for download. The method is compared to three baselines. ForCE manages to surpass all three.
UnivIS-Import:2015-10-26:Pub.2015.tech.IMMD.IMMD6.forcei
Keywords: Data quality; Population completeness; Time series; Forecasting

Health economic impact of a pulmonary artery pressure sensor for heart failure telemonitoring: a dynamic simulation - Kolominsky-Rabas, Peter; Kriza, Christine; Djanatliev, Anatoli; Meier, Florian; Uffenorde, Steffen; Radeleff, Jannis; Baumgärtel, Philipp; Leb, Ines; Sedlmayr, Martin; Gaiser, Sebastian; Adamson, Phil (Telemedicine Journal and E-Health, 2016)
AIMS: Recently, a permanently implantable wireless system, designed to monitor and manage pulmonary artery (PA) pressures remotely, demonstrated significant reductions in heart failure (HF) hospitalizations in high-risk symptomatic patients, regardless of ejection fraction. The objectives of this study were to simulate the estimated clinical and economic impact in Germany of generalized use of this PA pressure monitoring system considering reductions of HF hospitalizations and the improvement in Quality of Life. MATERIALS AND METHODS: Based on the Prospective Health Technology Assessment approach, we simulated the potential of the widespread application of PA pressure monitoring on the German healthcare system for the period 2009-2021. RESULTS: This healthcare economic simulation formulated input assumptions based on results from the CHAMPION Trial, a multicenter, prospective, randomized controlled U.S. trial that demonstrated a 37% reduction of hospitalizations in persistently symptomatic previous HF patients. Based on these results, an estimated 114,800 hospitalizations would expected to be avoided. This effect would potentially save an estimated €522 million, an equivalent of 575 million, during the entire simulation period. CONCLUSION: This healthcare economic modeling of the PA pressure monitoring system's impact demonstrates substantial clinical and economic benefits in the German healthcare system.
EVALuna2:33966
Keywords: to appear

Inverse Uncertainty Propagation for Demand Driven Data Acquisition - Baumgärtel, Philipp; Endler, Gregor; Wahl, Andreas Maximilian; Lenz, Richard (Proceedings of the 2014 Winter Simulation Conference, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD6.invers

Kalibrierung von Kostenmodellen für föderierte DSMS - Daum, Michael; Lauterwald, Frank; Baumgärtel, Philipp; Meyer-Wegener, Klaus (Proceedings BTW 2011 - Workshops und Studierendenprogramm, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD6.kalibr

Ökonomische Effekte durch den Einsatz von CardioMEMS bei herzinsuffizienten Patienten in Deutschland: das ProHTA-Simulationskonzept - Uffenorde, Steffen; Meier, Florian; Radeleff, Jannis; Djanatliev, Anatoli; Kriza, Christine; Baumgärtel, Philipp; Leb, Ines; Kolominsky-Rabas, Peter (Tagungsband der 7. Jahrestagung der Deutschen Gesellschaft für Gesundheitsökonomie, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.konomi

Pay-as-you-go data integration for large scale healthcare simulations - Baumgärtel, Philipp; Endler, Gregor; Held, Johannes; Lenz, Richard (GMDS 2012, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD6.payasy

Pay-as-you-go data quality improvement for medical centers - Endler, Gregor; Baumgärtel, Philipp; Lenz, Richard (Proceedings of the eHealth2013, 2013)
Medical practitioners often link their databases to support new use cases of the medical sector, e.g. in  economic  planning  or  treatment  coordination.  Data  quality  requirements  for  these  use  cases differ  from  the  original  requirements  on  the  databases.  We  argue  that  any  system  seeking  to support  data  quality  in  this  scenario  requires  significant  evolutionary  power.  We  suggest  an approach to continuously improve data quality which scales with arising requirements in a pay-as-you-go manner.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD6.payasy
Keywords: Data Quality Management; Demand-Driven Improvement

Propagation of Densities of Streaming Data within Query Graphs - Daum, Michael; Lauterwald, Frank; Baumgärtel, Philipp; Meyer-Wegener, Klaus (Scientific and Statistical Database Management: 22nd International Conference, 2010)
Data Stream SystemsDSS use cost models to determine if a DSS can cope with a given workload and to optimize query graphs. However, certain relevant input parameters of these models are often unknown or highly imprecise. Especially selectivities are stream-dependent and application-specific parameters. In this paper, we describe a method that supports selectivity estimation considering input streams' attribute value distribution. The novelty of our approach is the propagation of the probability distributions through the query graph in order to give estimates for the inner nodes of the graph. For most common stream operators, we establish formulas that describe their output distribution as a function of their input distributions. For unknown operators like User-Defined OperatorsUDO, we introduce a method to measure the influence of these operators on arbitrary probability distributions. This method is able to do most of the computational work before the query is deployed and introduces minimal overhead at runtime. Our evaluation framework facilitates the appropriate combination of both methods and allows to model almost arbitrary query graphs. © 2010 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD6.propag

Toward Pay-As-You-Go Data Integration for Healthcare Simulations - Baumgärtel, Philipp; Endler, Gregor; Lenz, Richard (Proceedings of the International Conference on Health Informatics, 2014)
ProHTA (Prospective Health Technology Assessment) aims at understanding the impact of innovative medical processes and technologies at an early stage. To that end, large scale healthcare simulations are employed to estimate the effects of potential innovations. Simulation techniques are also utilized to detect areas with a high potential for improving the supply chain of healthcare. The data needed for both validating and adjusting these simulations typically comes from various heterogeneous sources and is often preaggregated and insufficiently documented. Thus, new data management techniques are required to cope with these conditions. Because of the high initial integration effort, we propose a pay-as-you-go approach using RDF. Thereby, data storage is separated from semantic annotation. Our proposed system offers automatic initial integration of various data sources. Additionally, it provides methods for searching semantically annotated data and for loading it into the simulation. The user can add annotations to the data in order to enable semantic integration on demand. In this paper, we demonstrate the feasibility of this approach with a prototype implementation. We discuss benefits and remaining challenges. Copyright © 2014 SCITEPRESS - Science and Technology Publications. All rights reserved.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD6.toward
Keywords: Data integration; Data management; Healthcare; Simulation

Towards Data and Data Quality Management for Large Scale Healthcare Simulations - Baumgärtel, Philipp; Lenz, Richard (Proceedings of the International Conference on Health Informatics, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD6.toward

Towards data and data quality management for large scale healthcare simulations - Position Paper - Baumgärtel, Philipp; Lenz, Richard (HEALTHINF 2012 - Proceedings of the International Conference on Health Informatics, 2012)
Keywords: Knowledge management; Healthcare; Simulation data management; Ontologies

Verbesserte Integration von Medizintechnik durch Testdatenqualität - Held, Johannes; Endler, Gregor; Baumgärtel, Philipp; Lenz, Richard (GMDS 2012, 2012)